Electrostatic charge image developing toner, electrostatic charge image developer and toner cartridge

By using the electrostatically charged image development toner of the olefin resin containing polar groups, the problem of poor image bending resistance at low fixing temperatures is solved, and high image intensity and excellent bending resistance over a wide temperature range are achieved.

CN111752114BActive Publication Date: 2025-02-18FUJIFILM BUSINESS INNOVATION CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN201910861851.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-26
Filing Date
2019-09-12
Publication Date
2025-02-18
Estimated Expiration
2039-09-12

AI Technical Summary

Technical Problem

In the case where the toner image is fixed to a recording medium considered to be heat sensitive, it is necessary to lower the fixing temperature to obtain a high image intensity, but this results in poor bending resistance of the image.

Method used

An electrostatic charge image development toner containing an olefin resin containing a polar group, the resin is a polymer selected from the group consisting of ethylene and an α-olefin having 3 to 10 carbon atoms, having 10 mg KOH/ g to 60 mgKOH/g acid number.

Benefits of technology

The image to be formed has excellent bending resistance and maintains high image intensity over a wide temperature range, which solves the problem of poor bending resistance of the image after the fixing temperature is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111752114B_ABST
    Figure CN111752114B_ABST
Patent Text Reader

Abstract

An electrostatic charge image developing colorant, an electrostatic charge image developer, and a colorant box. An electrostatic charge image developing colorant includes: an olefin resin containing a polar group, which is a polymer of a composition comprising at least one non-polar monomer unit (X) selected from the group consisting of ethylene and α-olefins having 3 to 10 carbon atoms, a polar monomer unit (Y) having at least one of a maleic acid group and a maleic anhydride group, and a monomer unit (Z) having polymerizability with at least one of the non-polar monomer unit (X) and the polar monomer unit (Y), wherein the acid value of the toner is 10 mgKOH / g to 60 mgKOH / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrostatic charge image developing toner, an electrostatic charge image developer and a toner cartridge. Background Art

[0002] In the image forming apparatus, a toner image formed on the surface of an image holding member is transferred to the surface of a recording medium and then fixed on the recording medium by a fixing member heated and pressed in contact with the toner image to form an image.

[0003] As a toner used for such an image forming apparatus, for example, JP-A-2017-201398 discloses “a toner having toner particles containing a resin component, wherein the resin component contains an ester group-containing olefin copolymer and an acid group-containing olefin copolymer, the ester group-containing olefin copolymer has a unit Y1 of a specific structure, and at least one unit Y2 selected from the group consisting of a unit of a specific structure and a unit consisting of a unit of a specific structure, the acid value of the ester group-containing olefin copolymer is 10 mgKOH / g or more, the acid value of the acid group-containing olefin copolymer is 50 mgKOH / g to 300 mgKOH / g, the content of the ester group-containing olefin copolymer in the resin component is 50 wt % or more relative to the total mass of the resin component, and the content of the unit Y2 in the ester group-containing olefin copolymer is 3 wt % to 35 wt % relative to the total mass of the ester group-containing olefin copolymer”.

[0004] Furthermore, JP-A-2010-151899 discloses "an electrostatic charge image developing toner comprising a binder resin (A) containing at least an alicyclic olefin resin or a polyester resin, an α-olefin copolymer resin (B) ionically bonded between molecules via metal ions, and a colorant".

[0005] In addition, JP-A-2000-98664 discloses "an electronic photographic toner comprising: a copolymer comprising, as monomer components, an α-olefin monomer unit A for forming at least a specific structure and at least one monomer unit B selected from a vinyl monomer having a carboxyl group or an acid anhydride group; and a polyolefin resin having an ionically crosslinked structure obtained by reacting with a metal compound capable of ionically crosslinking with a carboxyl group or an acid anhydride group." Summary of the invention

[0006] In recent years, it is necessary to form images on various recording media (for example, recording media such as adhesive paper, film synthetic paper, and labels considered to be heat-sensitive). However, in the case of fixing a toner image to a recording medium considered to be heat-sensitive, it is necessary to lower the fixing temperature at the time of fixing, making it difficult to obtain high image strength. As a result, the obtained image may be inferior in bending resistance.

[0007] An object of the present invention is to provide an electrostatic charge image developing toner having excellent bending resistance in an image to be formed, compared with a case where an olefin resin is contained alone or a case where the acid value of the toner is less than 10 mgKOH / g, wherein the olefin resin is a polymer of a composition containing only two of the following: at least one nonpolar monomer unit (X) selected from the group consisting of ethylene and an α-olefin having 3 to 10 carbon atoms, a polar monomer unit (Y) having at least one of a maleic acid group and a maleic anhydride group, and a monomer unit (Z) having polymerizability with at least one of the nonpolar monomer unit (X) and the polar monomer unit (Y).

[0008] The above object is achieved by the following means.

[0009] <1>

[0010] According to one aspect of the present disclosure, there is provided an electrostatic charge image developing colorant, comprising an olefin resin containing a polar group, which is a polymer of a composition comprising at least one non-polar monomer unit (X) selected from the group consisting of ethylene and α-olefins having 3 to 10 carbon atoms, a polar monomer unit (Y) having at least one of a maleic acid group and a maleic anhydride group, and a monomer unit (Z) having polymerizability with at least one of the non-polar monomer unit (X) and the polar monomer unit (Y), wherein the acid value of the colorant is 10 mgKOH / g to 60 mgKOH / g.

[0011] <2>

[0012] according to <1> The electrostatic charge image developing toner, wherein the polar group-containing olefin resin is a polymer of a composition containing at least one selected from the group consisting of ethylene and α-olefins having 3 to 6 carbon atoms as the non-polar monomer unit (X).

[0013] <3>

[0014] according to <1> The electrostatic charge image developing toner, wherein the polar group-containing olefin resin is a polymer of a composition in which the ratio of the polar monomer unit (Y) relative to the total monomer units of the polymer is 1 wt % to 20 wt %.

[0015] <4>

[0016] according to <1> The electrostatic charge image developing toner, wherein the polar group-containing olefin resin is a polymer of a composition containing an acrylic acid ester represented by the molecular formula (Z1) as the monomer unit (Z), wherein the molecular formula (Z1) is 2 C=C(R Z1 )-COO-RZ2

[0017] R Z1 represents a methyl group or an ethyl group, and R Z2 represents an alkyl group having 1 to 6 carbon atoms.

[0018] <5>

[0019] according to <1> The electrostatic charge image developing toner, wherein the ratio of the polar group-containing olefin resin relative to the total mass of the resin components contained in the toner is 35 wt % to 100 wt %.

[0020] <6>

[0021] according to <1> The electrostatic charge image developing toner further comprises a polyester resin.

[0022] <7>

[0023] according to <1> The electrostatic charge image developing toner, wherein the melting temperature of the polar group-containing olefin resin is 65° C. to 95° C.

[0024] <8>

[0025] according to <1> The electrostatic charge image developing toner, wherein the ratio of the carboxyl groups contained in the maleic acid group and the maleic anhydride group among all the carboxyl groups contained in the electrostatic charge image developing toner is 10% to 100%.

[0026] <9>

[0027] According to another aspect of the present disclosure, there is provided an electrostatic charge image developer, the electrostatic charge image developer comprising <1> The electrostatic charge image developing toner.

[0028] <10>

[0029] According to another aspect of the present disclosure, a toner cartridge is provided, the toner cartridge being configured to accommodate <1> The electrostatic charge image developing toner, wherein the toner cartridge is detachable from the image forming apparatus.

[0030] According to <1> , <4> or <6> The present invention described in provides an electrostatic charge image developing toner having excellent bending resistance in an image to be formed, compared with a case where the toner contains only an olefin resin or a case where the acid value of the toner is less than 10 mgKOH / g, wherein the olefin resin is a polymer of a composition containing only two of the following: at least one non-polar monomer unit (X) selected from the group consisting of ethylene and an α-olefin having 3 to 10 carbon atoms, a polar monomer unit (Y) having at least one of a maleic acid group and a maleic anhydride group, and a monomer unit (Z) having polymerizability with at least one of the non-polar monomer unit (X) and the polar monomer unit (Y).

[0031] According to <2> The present invention described in provides an electrostatic charge image developing toner having excellent bending resistance in an image to be formed compared with the case where the polar group-containing olefin resin is a polymer of a composition containing only an α-olefin having 6 or more carbon atoms as a non-polar monomer unit (X).

[0032] According to <3> The present invention described in the text provides an electrostatic charge image developing toner having excellent bending resistance in an image to be formed, compared with the case where the polar group-containing olefin resin is a polymer of a composition in which the proportion of the polar monomer unit (Y) relative to all monomer units of the polymer is less than 1% by weight.

[0033] According to <5> The present invention described in provides an electrostatic charge image developing toner having excellent bending resistance in an image to be formed compared with the case where the proportion of the polar group-containing olefin resin relative to the total mass of the resin components contained in the toner is less than 35% by weight.

[0034] According to <7> The present invention described in provides an electrostatic charge image developing toner having excellent fixability in a wide temperature range compared with the case where the melting temperature of the polar group-containing olefin resin is higher than 95°C.

[0035] According to <7> The present invention described in provides an electrostatic charge image developing toner having excellent bending resistance in an image to be formed, compared with a case where the proportion of carboxyl groups contained in maleic acid groups and in maleic anhydride groups among all carboxyl groups contained in the electrostatic charge image developing toner is less than 10%.

[0036] According to <9> and <10> The present invention described in provides an electrostatic charge image developer or a toner cartridge having excellent bending resistance in an image to be formed, compared with the case where an electrostatic charge image developing toner containing an olefin resin is applied, or the case where an electrostatic charge image developing toner in which the acid value of the toner is less than 10 mgKOH / g is applied, wherein the olefin resin is a polymer of a composition containing only two of the following: at least one non-polar monomer unit (X) selected from the group consisting of ethylene and an α-olefin having 3 to 10 carbon atoms, a polar monomer unit (Y) having at least one of a maleic acid group and a maleic anhydride group, and a monomer unit (Z) having polymerizability with at least one of the non-polar monomer unit (X) and the polar monomer unit (Y). BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Exemplary embodiments of the present invention will be described in detail based on the following drawings, in which:

[0038] Figure 1 is a diagram showing a configuration of an image forming apparatus according to an exemplary embodiment; and

[0039] Figure 2 is a configuration diagram illustrating an example of a process cartridge according to this exemplary embodiment. DETAILED DESCRIPTION

[0040] Hereinafter, exemplary embodiments of the present invention will be described.

[0041] Electrostatic image developing toner

[0042] The electrostatic charge image developing toner (hereinafter referred to as "toner") according to the exemplary embodiment includes a polar group-containing olefin resin which is a polymer of a composition including the following nonpolar monomer unit (X), polar monomer unit (Y), and monomer unit (Z).

[0043] at least one non-polar monomer unit (X) selected from the group consisting of ethylene and α-olefins having 3 to 10 carbon atoms;

[0044] A polar monomer unit (Y) having at least one of a maleic acid group and a maleic anhydride group;

[0045] A monomer unit (Z) having polymerizability with at least one of a non-polar monomer unit (X) and a polar monomer unit (Y).

[0046] The acid value of the toner is 10 mgKOH / g to 60 mgKOH / g.

[0047] Note that as the monomer unit (Z), a monomer having a chemical structure different from those of the nonpolar monomer unit (X) and the polar monomer unit (Y) is used.

[0048] The toner according to the exemplary embodiment has the above-described configuration and thus has excellent resistance to bending in an image to be formed. The reason is presumed to be as follows.

[0049] In recent years, with the expansion of the printing market, the demand for forming images on various recording media (for example, recording media such as adhesive paper, film synthetic paper, and labels considered to be heat-sensitive) and the formation of images on plain paper and coated paper generally performed in the related art has been increasing. However, in order to achieve image formability on various recording media, fixability within a wide temperature range (so-called fixing latitude) is required, for example, in the case of fixing a toner image to a recording medium considered to be heat-sensitive, it is necessary to lower the fixing temperature at the time of fixing, so it is difficult to obtain high image strength. As a result, the obtained image may be inferior in bending resistance.

[0050] In contrast, the toner according to the exemplary embodiment includes an olefin resin containing a polar group, which is a polymer of a composition containing a non-polar monomer unit (X), a polar monomer unit (Y), and a monomer unit (Z) having a chemical structure different from the chemical structure of the non-polar monomer unit (X) and the polar monomer unit (Y). As described above, by including a resin in which at least three monomer units (X), (Y), and (Z) are polymerized, the fixability in a wide temperature range (so-called fixing latitude) is enhanced. Therefore, in the case of fixing a toner image to a recording medium that is considered to be sensitive to heat, that is, even in the case where it is necessary to lower the fixing temperature during fixing, the image strength in the fixed image is enhanced, and the bending resistance is excellent.

[0051] In addition, the olefin resin containing polar groups has at least one of maleic acid group and maleic anhydride group. These maleic acid group and maleic anhydride group have at least two carboxyl groups in each group, so in the polymer chain of the olefin resin containing polar groups, two carboxyl groups exist adjacent to each other. Hydrophilic polar groups such as carboxyl groups interact with recording media to help adhere to recording media. Therefore, due to the presence of two adjacent carboxyl groups in the polymer chain, adjacent carboxyl groups interact with recording media to firmly fix, thereby enhancing the image strength in the fixed image, and enhancing the bending resistance of the image.

[0052] In the toner according to the exemplary embodiment, the acid value of the toner is 60 mgKOH / g or less. That is, the toner contains a large amount of acid groups, and these acid groups interact with the recording medium to facilitate adhesion to the recording medium. Therefore, the image strength in the fixed image is enhanced, and the bending resistance of the image is enhanced.

[0053] As described above, according to the toner of the exemplary embodiment, the bending resistance of an image to be formed is excellent.

[0054] Furthermore, the toner according to the exemplary embodiment has the above-described configuration, thereby enhancing fixability in a wide temperature range (so-called fixing latitude), and enhancing low-temperature offset resistance and high-temperature offset resistance.

[0055] The reason is presumed to be as follows.

[0056] The toner according to the exemplary embodiment includes an olefin resin containing a polar group, and the olefin resin containing a polar group is a polymer of a composition of a monomer unit (Z) containing a non-polar monomer unit (X), a polar monomer unit (Y), and a chemical structure different from the chemical structure of the non-polar monomer unit (X) and the polar monomer unit (Y). As described above, by including a resin in which at least three monomer units (X), (Y) and (Z) are polymerized, the fixability in a wide temperature range (so-called fixing latitude) is enhanced. In addition, it is believed that the toner has appropriate flexibility while being elastic in a wide temperature range, so that excellent high temperature offset resistance and excellent low temperature offset resistance can be achieved. Utilizing this configuration, according to the toner according to the exemplary embodiment, the fixability in a wide temperature range is enhanced, and the low temperature offset resistance and high temperature offset resistance are enhanced.

[0057] Acid value

[0058] In the toner according to the exemplary embodiment, the acid value of the toner is 10 mgKOH / g to 60 mgKOH / g, more specifically, 12 mgKOH / g to 50 mgKOH / g, and further preferably 12 mgKOH / g to 30 mgKOH / g.

[0059] When the acid value of the toner is less than 10 mgKOH / g, the bending resistance of the image deteriorates, and cracks may occur when the image is bent. On the other hand, if the acid value is greater than 60 mgKOH / g, image defects may occur in a high temperature and high humidity environment (for example, in an environment of 30° C., 85%). It is believed that the reason for this is that the hygroscopicity of the resin becomes high due to the increase in the hydrophilic group, and cleaning failure occurs in a high temperature and high humidity environment.

[0060] The acid value of the toner is measured using the following method. The basic operation is based on JIS K-0070 (1992).

[0061] Accurately weigh 1.5g of the crushed sample, put the sample into a 300ml beaker, and dissolve it by adding 100ml of tetrahydrofuran (THF), toluene or dimethylbenzene. Adopt automatic titrator GT-100 (manufactured by Mitsubishi Chemical Co., Ltd.), use 0.1mol / l potassium hydroxide (KOH) ethanol solution to carry out potentiometric titration. The amount of KOH solution used at this time is set to A (ml). In addition, measure blank, and the amount of KOH solution used at this time is set to B (ml). According to these values, acid value is calculated by the following equation. In this equation, w represents the amount of the accurately weighed sample, and f represents the factor of KOH.

[0062] Acid value (mgKOH / g) = {(AB) × f × 5.61} / w

[0063] ●Recording medium

[0064] In an exemplary embodiment, from the viewpoint of improving the bending resistance of an image, it is preferred to form at least one of a hydrogen bond and an ionic bond as the interaction between the recording medium and the carboxyl group. That is, it is preferred to use a recording medium having a group capable of forming at least one of a hydrogen bond and an ionic bond with a carboxyl group on the surface.

[0065] Examples of recording media having a group capable of forming at least one of a hydrogen bond and an ionic bond with a carboxyl group on the surface include plain paper, coated paper coated with a coating material such as starch, PET film, and PP film such as synthetic paper (Yupopaper).

[0066] Hereinafter, a toner according to an exemplary embodiment will be described in detail.

[0067] The toner according to the exemplary embodiment is configured to include toner particles and, if necessary, an external additive.

[0068] Toner particles

[0069] The toner particles are configured to include a binder resin, and if necessary, a colorant, a releasing agent, and other additives.

[0070] Binder resin

[0071] Olefin resin containing polar groups

[0072] In an exemplary embodiment, a polymer including a composition of the following non-polar monomer unit (X), polar monomer unit (Y), and monomer unit (Z) is used as a binder resin.

[0073] at least one non-polar monomer unit (X) selected from the group consisting of ethylene and α-olefins having 3 to 10 carbon atoms;

[0074] A polar monomer unit (Y) having at least one of a maleic acid group and a maleic anhydride group; and

[0075] A monomer unit (Z) having polymerizability with at least one of a non-polar monomer unit (X) and a polar monomer unit (Y).

[0076] ●Non-polar monomer unit (X)

[0077] As the non-polar monomer unit (X), at least one selected from the group consisting of ethylene and α-olefins having 3 to 10 carbon atoms is used. Note that, as the non-polar monomer unit (X), from the viewpoint of improving the bending resistance of the image, it is preferable to use at least one selected from the group consisting of ethylene and α-olefins having 3 to 6 carbon atoms, and it is more preferable to use at least one selected from the group consisting of ethylene and α-olefins having 3 to 4 carbon atoms.

[0078] As the polar group-containing olefin resin, one kind or two or more kinds of nonpolar monomer units (X) may be used.

[0079] Polar monomer unit (Y)

[0080] As the polar monomer unit (Y), a monomer having at least one of a maleic acid group and a maleic anhydride group is used. That is, a monomer having at least one of the following structures (a) and (b) in its molecular structure is used.

[0081] (a) (b)

[0082] Examples of the polar monomer unit (Y) include maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride.

[0083] Among them, maleic anhydride and maleic acid are preferred from the viewpoint of improving the bending resistance of an image.

[0084] As the polar group-containing olefin resin, one kind or two or more kinds of polar monomer units (Y) may be used.

[0085] ●Monomer unit (Z)

[0086] The monomer unit (Z) is a monomer having polymerizability with at least one of the non-polar monomer unit (X) and the polar monomer unit (Y). Note that as the monomer unit (Z), a monomer having a chemical structure different from the chemical structure of the non-polar monomer unit (X) and the polar monomer unit (Y) is used.

[0087] Examples of the monomer unit (Z) include a monomer having an olefinic double bond (ie, a monomer having a [═C═C═] structure) and a monomer having a plurality of olefinic double bonds.

[0088] Examples of the monomer having an olefinic double bond include (meth)acrylic acid and (meth)acrylate esters.

[0089] Examples of the (meth)acrylates include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, pentyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-hydroxy-2-(2-methyl-2-methoxy)-1-propene.

[0063] In some embodiments, the present invention relates to alkyl (meth)acrylates such as styrene, cyclohexyl (meth)acrylate, and tert-butylcyclohexyl (meth)acrylate, aryl (meth)acrylates such as phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, tert-butylphenyl (meth)acrylate, and triphenyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, (meth)acrylamide, styrene, alkyl-substituted styrenes such as α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, and 4-ethylstyrene, halogen-substituted styrenes such as 2-chlorostyrene, 3-chlorostyrene, and 4-chlorostyrene, and vinylnaphthalene.

[0090] Furthermore, monomers having a plurality of olefinic double bonds can also be used.

[0091] Examples of monomers having multiple olefinic double bonds include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylenebis(meth)acrylamide, decanediol diacrylate, and glycidyl(meth)acrylate), polyester di(meth)acrylate, and 2-([1'-methylpropyleneamino]carboxyamino)ethyl methacrylate.

[0092] Examples of the monomer having three or more olefinic double bonds include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, and trimethylolpropane tri(meth)acrylate), tetra(meth)acrylate compounds (e.g., pentaerythritol tetra(meth)acrylate and oligoester (meth)acrylate), 2,2-bis(4-methacryloyloxy, polyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, and diaryl chlorendic acid.

[0093] In this specification, "(meth)acrylic acid" is an expression including "acrylic acid" and "methacrylic acid".

[0094] Here, as the monomer unit (Z), an acrylate represented by the molecular formula (Z1) is preferable from the viewpoint of low-temperature fixing property.

[0095] Molecular formula (Z1)H 2 C=C(R Z1 )-COO-R Z2

[0096] In the molecular formula (Z1), R Z1 represents a methyl group or an ethyl group, and R Z2 represents an alkyl group having 1 to 6 carbon atoms.

[0097] R in the molecular formula (Z1) Z2 More preferred is an alkyl group having 1 to 4 carbon atoms, and still more preferred is an alkyl group having 1 to 3 carbon atoms.

[0098] As the monomer unit (Z), among the acrylic esters represented by the molecular formula (Z1), methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate and n-hexyl (meth)acrylate are more preferably used.

[0099] As the polar group-containing olefin resin, one kind or two or more kinds of monomer units (Z) may be used.

[0100] ●The ratio of non-polar monomer units (X), polar monomer units (Y) and monomer units (Z)

[0101] In the polar group-containing olefin resin, the ratio of the nonpolar monomer unit (X) to all monomer units is preferably 70 to 90% by weight, more preferably 75 to 85% by weight, from the viewpoint of sharp melting characteristics during fixing.

[0102] In the polar group-containing olefin resin, from the viewpoint of improving the bending resistance of the image, the proportion of the polar monomer unit (Y) relative to all monomer units is 1 wt % to 20 wt %, more preferably 2 wt % to 17 wt %, and still more preferably 2 wt % to 10 wt %.

[0103] In the polar group-containing olefin resin, the ratio of the monomer unit (Z) relative to all monomer units is preferably 5 to 30% by weight, more preferably 10 to 20% by weight, from the viewpoint of coexistence of low-temperature fixability and heat resistance.

[0104] ●Physical properties of olefin resins or toners containing polar groups

[0105] The melting temperature of the polar group-containing olefin resin is preferably 65°C to 95°C, more preferably 70°C to 90°C, still more preferably 75°C to 85°C.

[0106] When the melting temperature of the polar group-containing olefin resin is 65° C. or higher, the storage stability of the toner is easily improved. On the other hand, when the melting temperature is 95° C. or lower, the low-temperature fixability of the toner may be high, and as a result, the fixability in a wide temperature range (so-called fixing latitude) is likely to be enhanced.

[0107] According to the method of measuring the melting temperature of the crystalline polyester resin described later, the melting temperature of the polar group-containing olefin resin is determined by the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121-1987 “Method of measuring transition temperature of plastics”.

[0108] The weight average molecular weight Mw of the polar group-containing olefin resin is preferably 20,000 to 300,000, more preferably 50,000 to 200,000.

[0109] Note that the weight average molecular weight Mw of the polar group-containing olefin resin is measured by gel permeation chromatography (GPC) according to a measuring method of the weight average molecular weight of an amorphous polyester resin described later.

[0110] In the toner according to the exemplary embodiment, from the viewpoint of improving the bending resistance of the image, the ratio of the carboxyl groups contained in the maleic acid group and the maleic anhydride group among all the carboxyl groups contained in the toner is preferably 10% to 100%, more preferably 30% to 100%, and more preferably 50% to 100%.

[0111] Note that the ratio of the carboxyl groups contained in the maleic acid group and the maleic anhydride group among all the carboxyl groups contained in the toner is calculated by extracting a resin from the toner and then identifying the acid groups in the extracted resin. The identification of the acid groups is performed by measuring the extracted resin by Fourier transform infrared spectroscopy (FT-IR) or nuclear magnetic resonance (NMR).

[0112] Here, a method of extracting the resin in the toner will be described.

[0113] The physical properties of the above-mentioned polar group-containing olefin resin may be measured for the resin extracted from the toner, or may be measured for the polar group-containing olefin resin as a raw material of the toner.

[0114] To extract the resin, first, the toner is dissolved in tetrahydrofuran (THF), toluene or xylene to remove the pigment that is not dissolved in the solvent. Thereafter, the release agent is separated from the solution by the difference in molecular weight (usually, the release agent has a lower molecular weight than the binder resin). Due to the difference in molecular weight, it can be separated by a chromatographic column. In this way, the resin is extracted from the toner.

[0115] In the toner according to the exemplary embodiment, the proportion of the polar group-containing olefin resin is preferably 35 wt % to 100 wt %, more preferably 40 wt % to 100 wt %, and even more preferably 55 wt % to 100 wt % relative to the total mass of the resin components contained in the toner.

[0116] When the ratio of the polar group-containing olefin resin is 35% by weight or more, the bending resistance of the image to be formed may be high. In addition, the fixability in a wide temperature range can be enhanced, and the low-temperature offset resistance and high-temperature offset resistance can be enhanced.

[0117] Other adhesive resins

[0118] In the toner according to the exemplary embodiment, in addition to the polar group-containing olefin resin, other resin may be used in combination as a binder resin.

[0119] Examples of the binder resin include vinyl resins formed from homopolymers of monomers such as styrene (e.g., styrene, p-chlorostyrene and α-methylstyrene), (meth)acrylates (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate and 2-ethylhexyl methacrylate), ethylenically unsaturated nitriles (e.g., acrylonitrile and methacrylonitrile), vinyl ethers (e.g., vinyl methyl ether and vinyl isobutyl ether), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone and vinyl isopropenyl ketone) and olefins (e.g., ethylene, propylene and butadiene), or copolymers obtained by combining two or more of these monomers.

[0120] As the binder resin, there are also exemplified non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins and modified rosins, mixtures of non-vinyl resins and vinyl resins, or graft polymers obtained by polymerizing vinyl monomers in the coexistence of these non-vinyl resins.

[0121] These binder resins may be used alone or in combination of two or more.

[0122] In the toner according to the exemplary embodiment, when other resin is used in combination as a binder resin in addition to the polar group-containing olefin resin, a polyester resin is preferred as the binder resin used in combination. When the polyester resin is included, the adhesion of the image can be improved.

[0123] Examples of polyester resins include well-known amorphous polyester resins. As the polyester resin, a crystalline polyester resin may be used in combination with an amorphous polyester resin. Here, the content of the crystalline polyester resin may be used in a range of 2 wt % to 40 wt % (preferably 2 wt % to 20 wt %) relative to the entire binder resin.

[0124] Furthermore, the "crystallinity" of a resin means having a clear endothermic peak rather than a stepwise endothermic change in differential scanning calorimetry (DSC), and specifically means that the half width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min).

[0125] On the other hand, "amorphous" of a resin means that the half width exceeds 10°C, a stepwise endothermic change is shown, or no clear endothermic peak is observed.

[0126] ●Amorphous polyester resin

[0127] Examples of the amorphous polyester resin include polycondensates of polyvalent carboxylic acids and polyols. As the amorphous polyester resin, a commercial product may be used or a synthetic product may be used.

[0128] Examples of the polyvalent carboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, and sebacic acid), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, and naphthalene dicarboxylic acid), and anhydrides thereof or lower alkyl esters thereof (having, for example, 1 to 5 carbon atoms). Among them, for example, aromatic dicarboxylic acids are preferred as the polyvalent carboxylic acid.

[0129] As the polyvalent carboxylic acid, a trivalent or higher carboxylic acid adopting a crosslinked structure or a branched structure may be used in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, and anhydrides thereof or lower alkyl esters thereof (having, for example, 1 to 5 carbon atoms).

[0130] The polyvalent carboxylic acids may be used alone or in combination of two or more.

[0131] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, and neopentyl glycol), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, and hydrogenated bisphenol A), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A and propylene oxide adducts of bisphenol A). Among them, for example, aromatic diols and alicyclic diols are preferably used as the polyol, and aromatic diols are more preferably used as the polyol.

[0132] As the polyol, a trivalent or higher polyol adopting a crosslinked structure or a branched structure may be used in combination with a diol. Examples of the trivalent or higher polyol include glycerin, trimethylolpropane, and pentaerythritol.

[0133] The polyols may be used alone or in combination of two or more.

[0134] The glass transition temperature Tg of the amorphous polyester resin is preferably in the range of 50°C to 80°C, more preferably in the range of 50°C to 65°C.

[0135] The glass transition temperature is obtained from a DSC curve obtained by differential scanning calorimetry (DSC). More specifically, the glass transition temperature is obtained according to the "extrapolated glass transition start temperature" described in the method for obtaining the glass transition temperature in JIS K 7121-1987 "Testing methods for transition temperature of plastics".

[0136] The weight average molecular weight Mw of the amorphous polyester resin is preferably in the range of 5,000 to 1,000,000, more preferably in the range of 7,000 to 500,000.

[0137] The number average molecular weight Mn of the amorphous polyester resin is preferably in the range of 2,000 to 100,000.

[0138] The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably in the range of 1.5 to 100, and more preferably in the range of 2 to 60.

[0139] The weight average molecular weight and number average molecular weight were measured by gel permeation chromatography (GPC). GPC & HLC-8120GPC manufactured by TOSOH CORPORATION was used as a measuring device, and TSK gel Super HM-M (15 cm) chromatographic column and THF solvent manufactured by TOSOH CORPORATION were used to carry out the molecular weight measurement of GPC. The weight average molecular weight and number average molecular weight were calculated by using a molecular weight calibration curve drawn using a monodisperse polystyrene standard sample according to the above measurement results.

[0140] The amorphous polyester resin is produced using a known production method. Specific examples thereof include a method in which a reaction is conducted at a polymerization temperature set within a range of 180° C. to 230° C., if necessary, under reduced pressure in a reaction system while removing water or alcohol generated during condensation.

[0141] When the monomers of the raw materials are insoluble or incompatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve the monomers. In this case, the polycondensation reaction is carried out while the solubilizing agent is distilled off. When there are monomers with poor compatibility in the copolymerization reaction, the monomers with poor compatibility and the acid or alcohol to be polycondensed with the monomers may be condensed in advance and then polycondensed with the main component.

[0142] ●Crystalline polyester resin

[0143] Examples of the crystalline polyester resin include polycondensates of polyvalent carboxylic acids and polyols. As the crystalline polyester resin, a commercial product may be used or a synthetic product may be used.

[0144] Here, the crystalline polyester resin is preferably a condensate using a polymerizable monomer having a linear aliphatic group rather than a polymerizable monomer having an aromatic group in order to easily form a crystal structure.

[0145] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid), aromatic dicarboxylic acids (e.g., phthalic acid, isophthalic acid, terephthalic acid, dibasic acids such as naphthalene-2,6-dicarboxylic acid), and anhydrides thereof or lower alkyl esters thereof (having, for example, 1 to 5 carbon atoms).

[0146] As the polyvalent carboxylic acid, a trivalent or higher carboxylic acid adopting a cross-linked structure or a branched structure can be used in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, and 1,2,4-naphthalenetricarboxylic acid) and anhydrides thereof or lower alkyl esters thereof (having, for example, 1 to 5 carbon atoms).

[0147] As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an olefinic double bond can be used in combination with these dicarboxylic acids.

[0148] The polyvalent carboxylic acids may be used alone or in combination of two or more.

[0149] Examples of the polyol include aliphatic diols (eg, linear aliphatic diols having 7 or more and 20 or less carbon atoms in the main chain portion).

[0150] Examples of the aliphatic diol include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosandiol. Among them, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferably used as the aliphatic diol.

[0151] As the polyol, a trivalent or higher valent alcohol having a cross-linked structure or a branched structure can be used in combination with a diol. Examples of trivalent or higher valent alcohols include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyol can be used alone or in combination of two or more.

[0152] Here, the polyol preferably has an aliphatic diol content of 80 mol % or more, and more preferably has an aliphatic diol content of 90 mol % or more.

[0153] The melting temperature of the crystalline polyester resin is preferably 50°C to 100°C, more preferably 55°C to 90°C, still more preferably 60°C to 85°C.

[0154] Note that the melting temperature is obtained from a DSC curve obtained by differential scanning calorimetry (DSC), and specifically, is obtained according to the “melting peak temperature” described in the method for obtaining the melting temperature in JIS K 7121-1987 “Testing methods for transition temperatures of plastics”.

[0155] The weight average molecular weight Mw of the crystalline polyester resin is preferably 6,000 to 35,000.

[0156] Similar to the amorphous polyester resin, the crystalline polyester resin can be obtained by a known production method.

[0157] The content of the entire binder resin including the polar group-containing olefin resin is, for example, preferably 40 to 95 wt %, more preferably 50 to 90 wt %, and still more preferably 60 to 85 wt % relative to the entire toner particles.

[0158] Colorants

[0159] Examples of the colorant include various types of pigments such as carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Varacan orange, watch red, permanent red, brilliant carmine 3B, brilliant carmine 6B, Dupont Oil Red, pyrazolone red, lithotripter red, rhodamine B Lake, Red Lake C, pigment red, rose bengal, aniline blue, ultramarine blue, calco oil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate, or various types of dyes such as acridine dyes, xanthene dyes, azo dyes, benzoquinone dyes, azine dyes, anthraquinone dyes, thioindigo dyes, dioxazine dyes, thiazine dyes, azomethine dyes, indigo dyes, phthalocyanine dyes, aniline black dyes, polymethine dyes, triphenylmethane dyes, diphenylmethane dyes, and thiazole dyes.

[0160] In addition, a white pigment may be included as a colorant. Examples of white pigments include titanium oxide (such as titanium oxide particles having anatase type and titanium oxide particles having rutile type), barium sulfate, zinc oxide, and calcium carbonate. Among them, titanium oxide is preferred as a white pigment.

[0161] In addition, a bright color pigment may be included as a colorant. Examples of the bright color pigment include pearlescent pigment powder, aluminum powder, metal powder such as stainless steel powder, metal flakes, glass beads, glass flakes, mica, and mica iron oxide.

[0162] The coloring agents may be used alone or in combination of two or more.

[0163] As the colorant, a surface-treated colorant may be used, if necessary, and it may be used together with a dispersant. In addition, a plurality of colorants may be used in combination.

[0164] The content of the colorant is preferably 1% by weight to 30% by weight, more preferably 3% by weight to 15% by weight, relative to the entire toner particles.

[0165] Release agent

[0166] Examples of the release agent include hydrocarbon wax, natural wax such as carnauba wax, rice wax and candelilla wax, synthetic wax or mineral wax or petroleum wax such as montan wax, and ester wax such as fatty acid ester and montanic acid ester. However, the release agent is not limited to the above examples.

[0167] The melting temperature of the releasing agent is preferably in the range of 50°C to 110°C, and further preferably in the range of 60°C to 100°C.

[0168] Note that the melting temperature is obtained from a DSC curve obtained by differential scanning calorimetry (DSC), and specifically, is obtained according to the “melting peak temperature” described in the method for obtaining the melting temperature in JIS K 7121-1987 “Testing methods for transition temperatures of plastics”.

[0169] The content of the releasing agent is preferably from 1% by weight to 20% by weight, more preferably from 5% by weight to 15% by weight, relative to the entire toner particles.

[0170] Other additives

[0171] Examples of other additives include well-known additives such as magnetic materials, electrostatic charge control agents, and inorganic powders. These additives are contained in toner particles as internal additives.

[0172] Properties of toner particles

[0173] The toner particles may be toner particles having a single-layer structure, or toner particles having a so-called core and shell structure consisting of a core (so-called core particle) and a coating layer (so-called shell layer) coated on the core.

[0174] Here, the toner particles having a core and shell structure are preferably composed of, for example, a core containing a binder resin, and, if necessary, other additives such as a colorant and a releasing agent, and a coating layer containing a binder resin.

[0175] The volume average particle diameter D50v of the toner particles is preferably from 2 μm to 10 μm, more preferably from 4 μm to 8 μm.

[0176] Various average particle diameters and various particle diameter distribution indices of the toner particles are measured using a Coulter Counter II (manufactured by Beckman Coulter, Inc.), and the electrolyte solution is measured using ISOTON-II (manufactured by Beckman Coulter, Inc.).

[0177] In the measurement, a measurement sample in the range of 0.5 mg to 50 mg is added as a dispersant to 2 ml of a 5% aqueous surfactant solution, preferably sodium alkylbenzene sulfonate. The resulting material is added to an electrolyte in the range of 100 ml to 150 ml.

[0178] The electrolyte in which the sample was suspended was subjected to a dispersion treatment for one minute using an ultrasonic disperser, and the particle size distribution of particles having a particle size of 2 to 60 μm was measured by a Coulter Counter II using an aperture having an aperture of 100 μm. 50,000 particles were sampled.

[0179] The cumulative distribution of volume and number is plotted from the minimum diameter side with respect to the particle size range (so-called channel) separated based on the measured particle size distribution. The particle size corresponding to the cumulative percentage of 16% is defined as the particle size corresponding to the volume average particle size D16v and the number average particle size D16p, and the particle size corresponding to the cumulative percentage of 50% is defined as the particle size corresponding to the volume average particle size D50v and the number average particle size D50p. In addition, the particle size corresponding to the cumulative percentage of 84% is defined as the particle size corresponding to the volume average particle size D84v and the number average particle size D84p.

[0180] Using these data, the volume particle size distribution index (GSDv) is calculated as (D84v / D16v) 1 / 2 , and the particle size distribution index (GSDp) is calculated as (D84p / D16p) 1 / 2 .

[0181] The average circularity of the toner particles is preferably from 0.94 to 1.00, more preferably from 0.95 to 0.98.

[0182] The average circularity of the toner particles is calculated by (circumference of circle equivalent diameter) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, the above value is measured by using the following method.

[0183] The average circularity of the toner particles was calculated by using a flow particle image analyzer (FPIA-3000 manufactured by Sysmex Co., Ltd.) which first sucks and collects the toner particles to be measured to form a flake flow, then captures the particle image as a static image by instantaneously emitting a flash, and then performs image analysis on the obtained particle image. 3500 particles were sampled when calculating the average circularity.

[0184] In the case where the toner contains an external additive, a developer containing the toner to be measured is dispersed in water containing a surfactant, and then the water is subjected to ultrasonic treatment to obtain toner particles from which the external additive is removed.

[0185] External additives

[0186] Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO 2 、TiO 2 、Al 2 O 3 , CuO, ZnO, SnO 2 、CeO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O、Na 2 O, ZrO 2 、CaO·SiO 2 , K 2 O·(TiO 2 )n、Al 2 O 3 ·2SiO 2 、CaCO 3 MgCO 3 ,BaSO 4 and MgSO 4 .

[0187] The surface of the inorganic particles as external additives can be subjected to hydrophobic treatment. The hydrophobic treatment is performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These hydrophobic treatment agents can be used alone or in combination of two or more.

[0188] The amount of the hydrophobizing agent is generally, for example, 1 to 10 parts by weight relative to 100 parts by weight of the inorganic particles.

[0189] Examples of the external additive include resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin, detergents such as higher fatty acid metal salts represented by zinc stearate, and particles of fluorine-based polymers.

[0190] The content of the external additive is preferably 0.01% by weight to 5% by weight, more preferably 0.01% by weight to 2.0% by weight, relative to the entire toner particles.

[0191] Toner production method

[0192] Next, a method of producing a toner according to the exemplary embodiment will be described.

[0193] The toner according to the exemplary embodiment may be obtained by producing toner particles and then externally adding an external additive to the toner particles.

[0194] Toner particles can be produced by using any of dry methods (eg, kneading and pulverization) and wet methods (eg, aggregation and coalescence, suspension polymerization, and dissolution suspension). The production method of the toner particles is not particularly limited, and a known method can be used.

[0195] Among them, toner particles can be obtained by using an aggregation method and a coalescence method.

[0196] Specifically, for example, in the case of producing toner particles by using an aggregation method and a coalescence method, toner particles are produced by the following steps including a step of preparing a resin particle dispersion in which resin particles constituting a binder resin are dispersed (resin particle dispersion preparation step), a step of forming aggregated particles by aggregating resin particles (and, if necessary, other particles) in the resin particle dispersion (and, if necessary, in a dispersion in which other particle dispersions are mixed) (aggregate particle formation step), and a step of preparing toner particles by heating the aggregated particle dispersion in which the aggregated particles are dispersed to aggregate the aggregated particles to form toner particles (coalescence step).

[0197] Hereinafter, each step will be described in detail.

[0198] In the following description, a method of obtaining toner particles including a colorant and a release agent will be described; however, if necessary, a colorant and a release agent may be used. Other additives other than the colorant and the release agent may also be used.

[0199] Resin particle dispersion preparation steps

[0200] First, for example, a resin particle dispersion in which resin particles corresponding to the binder resin are dispersed, a colorant particle dispersion in which colorant particles are dispersed, and a releasing agent particle dispersion in which releasing agent particles are dispersed are prepared.

[0201] Here, the resin particle dispersion is prepared, for example, by dispersing the resin particles in a dispersion medium using a surfactant.

[0202] For example, an aqueous medium is used as the dispersion medium used in the resin particle dispersion.

[0203] Examples of the aqueous medium include water (such as distilled water, ion-exchanged water, etc.), alcohols, etc. The medium may be used alone or in combination of two or more.

[0204] Examples of surfactants include anionic surfactants such as sulfates, sulfonates, phosphates and soap anionic surfactants; cationic surfactants such as amine salts and quaternary ammonium salt cationic surfactants; and nonionic surfactants such as polyethylene glycol, alkylphenol ethylene oxide adducts and polyols. Among these surfactants, anionic surfactants and cationic surfactants are particularly preferably used. Nonionic surfactants can be used in combination with anionic surfactants or cationic surfactants.

[0205] The surfactants may be used alone or in combination of two or more.

[0206] In the resin particle dispersion, as a method for dispersing the resin particles in the dispersion medium, a general dispersion method by using, for example, a rotary shearing type homogenizer, a ball mill with a medium, a sand mill, or a Dyno mill is exemplified. In addition, depending on the type of the resin particles, the resin particles may be dispersed in the resin particle dispersion by using, for example, a phase inversion emulsification method.

[0207] The phase inversion emulsification method is a method of dispersing a resin in an aqueous medium in the form of particles by dissolving the resin to be dispersed in a hydrophobic organic solvent in which the resin is soluble, neutralizing by adding a base to an organic continuous phase (O phase), and performing inversion of the resin from W / O to O / W (so-called phase inversion) by adding an aqueous medium (W phase) to prepare a discontinuous phase.

[0208] The volume average particle diameter of the resin particles dispersed in the resin particle dispersion is, for example, preferably 0.01 μm to 1 μm, more preferably 0.08 μm to 0.8 μm, and still more preferably 0.1 μm to 0.6 μm. With respect to the volume average particle diameter of the resin particles, the cumulative distribution of the volume is plotted from the minimum diameter side with respect to the particle diameter range (so-called channel) separated using the particle diameter distribution obtained by measurement using a laser diffraction type particle diameter distribution measuring device (for example, manufactured by Horiba, Ltd., LA-700), and the particle diameter corresponding to the cumulative percentage of 50% with respect to the entire particles is set as the volume average particle diameter D50v. Note that the volume average particle diameter of particles in other dispersions is also measured in the same manner.

[0209] The content of the resin particles contained in the resin particle dispersion is preferably from 5% by weight to 50% by weight, and more preferably from 10% by weight to 40% by weight.

[0210] Note that the colorant particle dispersion and the release agent particle dispersion are also prepared in the same manner as the resin particle dispersion. That is, the volume average particle diameter of the particles in the resin particle dispersion, the dispersion medium, the dispersion method, and the particle content are the same as those of the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.

[0211] Aggregate particle formation step

[0212] Next, the resin particle dispersion, the colorant particle dispersion, and the releasing agent particle dispersion are mixed with one another.

[0213] Furthermore, in the mixed dispersion, the resin particles, the colorant particles, and the releasing agent particles are heteroaggregated to form aggregated particles having a diameter close to the target diameter of the toner particles and containing the resin particles, the colorant particles, and the releasing agent particles.

[0214] Specifically, for example, an aggregating agent is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to be acidic (for example, pH 2 to 5). If necessary, a dispersion stabilizer is added. Then, the mixed dispersion is heated at a temperature close to the glass transition temperature of the resin particles (specifically, for example, within the range of the glass transition temperature of the resin particles of -30°C to -10°C) to aggregate the particles dispersed in the mixed dispersion, thereby forming aggregated particles.

[0215] In the aggregated particle formation step, for example, an aggregating agent can be added at room temperature (e.g., 25° C.) while stirring the mixed dispersion using a rotary shearing type homogenizer, the pH of the mixed dispersion can be adjusted to acidic (e.g., pH 2 to 5), a dispersion stabilizer can be added if necessary, and then heating can be performed.

[0216] Examples of aggregating agents include surfactants having opposite polarity to the surfactant as a dispersant to be added to the mixed dispersion, inorganic metal salts, divalent or multivalent metal complexes. In particular, when a metal complex is used as an aggregating agent, the amount of surfactant used is reduced and the charging performance is improved. If necessary, an additive that forms a complex or a similar bond with a metal ion can be used as an aggregating agent. A chelating agent is suitable for use as an additive.

[0217] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate, and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.

[0218] As the chelating agent, an aqueous chelating agent may be used. Examples of the chelating agent include oxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid, iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).

[0219] The addition amount of the chelating agent is, for example, preferably in the range of 0.01 parts by weight to 5.0 parts by weight, and more preferably equal to or greater than 0.1 parts by weight and less than 3.0 parts by weight, relative to 100 parts by weight of the resin particles.

[0220] Coalescence step

[0221] Next, the aggregated particle dispersion in which the aggregated particles are dispersed is heated at a temperature equal to or higher than the glass transition temperature of the resin particles (eg, 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to coalesce the aggregated particles and form toner particles.

[0222] Toner particles are obtained through the aforementioned steps.

[0223] Note that the toner particles can be obtained by the following steps: a step of obtaining an aggregated particle dispersion in which aggregated particles are dispersed, mixing the aggregated particle dispersion and a resin particle dispersion in which resin particles are dispersed, and aggregating the mixture to form second aggregated particles in a manner such that the resin particles are attached to the surfaces of the aggregated particles, and a step of forming toner particles having a core and shell structure by heating the second aggregated particle dispersion in which the second aggregated particles are dispersed and agglomerating the second aggregated particles.

[0224] Here, after the coalescence step is finished, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step, thereby obtaining dried toner particles.

[0225] In the washing step, from the viewpoint of charging characteristics, displacement washing using ion exchange water can be sufficiently performed. In addition, the solid-liquid separation step is not particularly limited, but from the viewpoint of productivity, suction filtration, pressure filtration, etc. are preferably performed. The method of the drying step is also not particularly limited, but from the viewpoint of productivity, freeze drying, airflow drying, fluidized drying, vibration type fluidized drying, etc. can be performed.

[0226] The toner according to the exemplary embodiment is produced, for example, by adding an external additive to the toner particles obtained in a dry state and mixing them. The mixing can be performed by using, for example, a V-type mixer, a Henschel mixer, a Loedige mixer, etc. In addition, if necessary, coarse particles of the toner can be removed by using a vibration sieving machine, a wind classifier, etc.

[0227] Electrostatic charge image developer

[0228] The electrostatic charge image developer according to the exemplary embodiment includes at least the toner according to the exemplary embodiment. The electrostatic charge image developer according to the exemplary embodiment may be a single-component developer including only the toner according to the exemplary embodiment, or may be a two-component developer in which the toner and the carrier are mixed with each other.

[0229] The carrier is not particularly limited, and a known carrier can be used. Examples of the carrier include: a coated carrier in which the surface of the core formed of magnetic particles is coated with a coating resin; a magnetic particle dispersed carrier in which the magnetic particles are dispersed and distributed in a matrix resin; and a resin impregnated carrier in which a resin is impregnated into porous magnetic particles.

[0230] Note that the magnetic particle dispersed carrier and the resin impregnated carrier may be carriers in which the forming particles of the foregoing carrier are provided as cores and the cores are coated with a coating resin.

[0231] Examples of magnetic particles include magnetic metals such as iron, nickel, and cobalt, and magnetic oxides such as ferrite and magnetite.

[0232] Examples of the coating resin and the base resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, a linear silicone resin formed by containing an organic siloxane bond or a modified product thereof, a fluororesin, a polyester, a polycarbonate, a phenolic resin, and an epoxy resin. Note that other additives such as conductive particles may be contained in the coating resin and the base resin.

[0233] Examples of the conductive particles include metals such as gold, silver, and copper, and particles such as carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.

[0234] Here, in order to coat the surface of the core with the coating resin, a method of coating the surface with a coating forming solution is used, in which the coating resin and various additives (if necessary) are dissolved in an appropriate solvent. The solvent is not particularly limited as long as the solvent is selected in consideration of the coating resin to be used and coating suitability.

[0235] Specific examples of the resin coating method include an immersion method in which the core is immersed in a coating-forming solution, a spraying method in which the coating-forming solution is sprayed onto the surface of the core, a fluidized bed method in which the coating-forming solution is sprayed onto the core in a state of being floated by fluid air, and a kneading coating method in which the core of the carrier is mixed with the coating-forming solution and the solvent is removed in a kneading coater.

[0236] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, more preferably 3:100 to 20:100.

[0237] Image forming apparatus and image forming method

[0238] An image forming apparatus and an image forming method according to exemplary embodiments will be described.

[0239] The image forming apparatus according to the exemplary embodiment is provided with: an image holding member; a charging unit that charges the surface of the image holding member; an electrostatic charge image forming unit that forms an electrostatic charge image on the charged surface of the image holding member; a developing unit that contains an electrostatic charge image developer and develops the electrostatic charge image formed on the surface of the image holding member into a toner image by using the electrostatic charge image developer; a transfer unit that transfers the toner image formed on the surface of the image holding member to the surface of a recording medium; and a fixing unit that fixes the toner image transferred to the surface of the recording medium. In addition, the electrostatic charge image developer according to the exemplary embodiment is used as the electrostatic charge image developer.

[0240] In an image forming device according to an exemplary embodiment, an image forming method (an image forming method according to an exemplary embodiment) includes the following steps: charging the surface of an image holding member; forming an electrostatic charge image on the charged surface of the image holding member; developing the electrostatic charge image formed on the surface of the image holding member into a colorant image using an electrostatic charge image developer according to an exemplary embodiment; transferring the colorant image formed on the surface of the image holding member onto the surface of a recording medium; and fixing the colorant image transferred to the surface of the recording medium.

[0241] As an image forming device according to an exemplary embodiment, a known image forming device such as includes: a direct transfer type device, which directly transfers the colorant image formed on the surface of the image holding member to a recording medium; an intermediate transfer type device, which primarily transfers the colorant image formed on the surface of the image holding member to the surface of the intermediate transfer body, and secondarily transfers the colorant image transferred to the surface of the intermediate transfer body to the surface of the recording medium; a device including a cleaning unit, which cleans the surface of the image holding member before charging and after the toner image is transferred; and a device including an erasing unit, which erases the charge by irradiating the surface of the image holding member with erasing light before charging and after the toner image is transferred.

[0242] In the case of using an intermediate transfer type device, the transfer unit is configured to include: an intermediate transfer body that transfers the colorant image onto a surface; a first transfer unit that primarily transfers the colorant image formed on the surface of the image holding member onto the surface of the intermediate transfer body; and a second transfer unit that secondarily transfers the colorant image formed on the surface of the intermediate transfer body onto the surface of the recording medium.

[0243] In the image forming apparatus according to the exemplary embodiment, for example, the unit including the developing unit may be a cartridge structure (processing cartridge) detachable from the image forming apparatus. As the processing cartridge, for example, a processing cartridge including a developing unit accommodating the electrostatic charge image developer according to the exemplary embodiment is preferably used.

[0244] Hereinafter, an example of an image forming apparatus according to an exemplary embodiment will be described. However, the process cartridge is not limited thereto. The main parts shown in the drawings will be described, but description of other parts will be omitted.

[0245] Figure 1 is a diagram showing a configuration of an image forming apparatus according to an exemplary embodiment.

[0246] like Figure 1The image forming apparatus shown is provided with an electrophotographic first image forming unit 10Y, a second image forming unit 10M, a third image forming unit 10C, and a fourth image forming unit 10K (image forming means), which output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter referred to simply as "units" in some cases) 10Y, 10M, 10C, and 10K are arranged in parallel at a predetermined distance in the horizontal direction. Note that these units 10Y, 10M, 10C, and 10K may be process cartridges attached to and detached from the image forming apparatus.

[0247] On the upper side of each unit 10Y, 10M, 10C, and 10K in the figure, an intermediate transfer belt 20 as an intermediate transfer body extends through each unit. The intermediate transfer belt 20 is wound around a driving roller 22 and a supporting roller 24 that are in contact with the inner surface of the intermediate transfer belt 20, and travels in a direction toward the first unit 10Y to the fourth unit 10K, wherein the driving roller 22 and the supporting roller 24 are spaced apart from each other in the direction from left to right in the figure. A force is applied to the supporting roller 24 in a direction away from the driving roller 22 by a spring or the like (not shown), and tension is applied to the intermediate transfer belt 20 wound around the two rollers.

[0248] The intermediate transfer body cleaning device 30 is provided on the side surface of the image holding member of the intermediate transfer belt 20 so as to face the driving roller 22. In addition, toners including four color toners of yellow, magenta, cyan and black contained in the toner cartridges 8Y, 8M, 8C and 8K in the developers (developing units) 4Y, 4M, 4C and 4K of the respective units 10Y, 10M, 10C and 10K are provided.

[0249] Since the first unit 10Y to the fourth unit 10K have the same configuration, here, the first unit 10Y for forming a yellow image disposed on the upstream side in the traveling direction of the intermediate transfer belt will be described as a representative. The description of the second unit 10M, the third unit 10C, and the fourth unit 10K may be omitted by replacing the same parts as those in the first unit 10Y with reference numerals of magenta (M), cyan (C), and black (K) instead of yellow (Y).

[0250] The first unit 10Y includes a photoreceptor 1Y serving as an image holding member. Arranged in order around the photoreceptor 1Y are: a charging roller (an example of a charging unit) 2Y that charges the surface of the photoreceptor 1Y to a predetermined potential; an exposure device (an example of an electrostatic charge image forming unit) 3 that forms an electrostatic charge image by exposing the charged surface with a laser beam 3Y based on a color separation image signal; a developer (an example of a developing unit) 4Y that develops the electrostatic charge image by supplying a charged toner to the electrostatic charge image; a first transfer roller 5Y (an example of a first transfer unit) that transfers the developed toner image onto the intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning unit) 6Y that removes the toner remaining on the surface of the photoreceptor 1Y after the first transfer.

[0251] The first transfer roller 5Y is disposed on the inner side of the intermediate transfer belt 20 and is disposed at a position facing the photoreceptor 1Y. In addition, a bias power supply (not shown) for applying a first transfer bias is connected to each of the first transfer rollers 5Y, 5M, 5C, and 5K. Each bias power supply changes the transfer bias applied to each first transfer roller under the control of a control unit (not shown).

[0252] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.

[0253] By conducting (for example, the volume resistivity at 20°C is: 1×10 -6 The photoreceptor 1Y is formed by laminating a photosensitive layer on a substrate (Ωcm or less). The photosensitive layer generally has a high resistance (resistance of a general resin), but has a characteristic that when the laser beam 3Y is irradiated, the specific resistance of the portion irradiated by the laser beam changes. Therefore, according to the image data for yellow sent from the control unit (not shown), the laser beam 3Y is output to the surface of the charged photoreceptor 1Y through the exposure device 3. The laser beam 3Y is applied to the photosensitive layer on the surface of the photoreceptor 1Y, thereby forming an electrostatic charge image of a yellow image pattern on the surface of the photoreceptor 1Y.

[0254] The electrostatic charge image is an image formed on the surface of the photoreceptor 1Y by charging, and is a so-called negative latent image formed in the following manner: the resistivity of the irradiated portion of the photosensitive layer is reduced by the laser beam 3Y, and the charge charged on the surface of the photoreceptor 1Y flows, while the charge of the portion not irradiated by the laser beam 3Y remains.

[0255] The electrostatic charge image formed on the photoreceptor 1Y rotates to a predetermined developing position as the photoreceptor 1Y travels. Then, at the developing position, the electrostatic charge image on the photoreceptor 1Y is made visible as a toner image (developed image) by the developing device 4Y.

[0256] For example, in the developer 4Y, an electrostatic charge image developer containing at least a yellow toner and a carrier is accommodated. The yellow toner is frictionally charged by being stirred in the developer 4Y, and is held on a developer roller (an example of a developer holding body) with a charge of the same polarity (negative polarity) as the charge on the photoreceptor 1Y. Then, when the surface of the photoreceptor 1Y passes through the developer 4Y, the yellow toner is electrostatically attached to the discharged latent image portion on the surface of the photoreceptor 1Y, and the latent image is developed by the yellow toner. The photoreceptor 1Y on which the yellow toner image is formed then travels at a predetermined speed, and the toner image developed on the photoreceptor 1Y is conveyed to a predetermined first transfer position.

[0257] When the yellow toner image on the photoreceptor 1Y is conveyed to the first transfer position, the first transfer bias is applied to the first transfer roller 5Y, the electrostatic force from the photoreceptor 1Y toward the first transfer roller 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time is a (+) polarity opposite to the (-) polarity of the toner, and is controlled to +10 μA by a control unit (not shown) in the first unit 10Y, for example.

[0258] On the other hand, the toner remaining on the photoreceptor 1Y is removed and collected by the photoreceptor cleaning device 6Y.

[0259] Furthermore, the first transfer bias applied to the first transfer rollers 5M, 5C, and 5K after the second unit 10M is also controlled according to the first unit.

[0260] Thus, the intermediate transfer belt 20 to which the yellow toner image is transferred in the first unit 10Y is transported sequentially through the second unit 10M, the third unit 10C, and the fourth unit 10K, and the toner images of the respective colors are superimposed and transferred multiple times.

[0261] The intermediate transfer belt 20 on which the toner images of four colors are transferred multiple times through the first to fourth units leads to a second transfer section configured to include the intermediate transfer belt 20 and a support roller 24 in contact with the inner surface of the intermediate transfer belt, and a second transfer roller (an example of a second transfer device) 26 provided on the image holding surface side of the intermediate transfer belt 20. On the other hand, a recording paper (an example of a recording medium) P is fed to a gap in which the second transfer roller 26 and the intermediate transfer belt 20 are in contact with each other via a feeding mechanism at a predetermined timing, and a second transfer bias is applied to the support roller 24. The transfer bias applied at this time is the same as the polarity (-) of the toner, and an electrostatic force from the intermediate transfer belt 20 to the recording paper P acts on the toner image, so that the toner image is transferred to the recording paper P on the intermediate transfer belt 20. The second transfer bias at this time is determined based on the resistance detected by a resistance detection unit (not shown) that detects the resistance of the second transfer section, and is voltage-controlled.

[0262] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rollers in a fixing device (example fixing unit) 28 , the toner image is fixed on the recording paper P, and a fixed image is formed.

[0263] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copiers, printers, and the like. As the recording medium, in addition to the recording paper P, OHP paper and the like can be exemplified. In order to further improve the smoothness of the image surface after fixing, the surface of the recording paper P is also preferably smooth, and for example, coated paper in which the surface of plain paper is coated with a resin or the like and art paper for printing are preferably used.

[0264] The recording paper P on which the color image fixing is completed is transported to the discharge portion, and a series of color image forming operations are completed.

[0265] Process cartridges and toner cartridges

[0266] A process cartridge according to an exemplary embodiment will be described. The process cartridge according to the exemplary embodiment is provided with a developing unit that accommodates an electrostatic charge image developer according to the exemplary embodiment, develops an electrostatic charge image formed on the surface of an image holding member into a toner image with the electrostatic charge image developer, and is detachable from an image forming apparatus.

[0267] The process cartridge according to the exemplary embodiment is not limited to the above-described configuration, and may be configured to include a developer and at least one selected from other units such as an image holding member, a charging unit, an electrostatic charge image forming unit, and a transfer unit.

[0268] Hereinafter, an example of a process cartridge according to this exemplary embodiment will be described. However, the process cartridge is not limited thereto. The main parts shown in the drawings will be described, but description of other parts will be omitted.

[0269] Figure 2 is a configuration diagram illustrating an example of a process cartridge according to this exemplary embodiment.

[0270] Figure 2 The processing box 200 shown is configured so that the photosensitive body 107 (an example of an image holding member), a charging roller 108 (an example of a charging unit) arranged near the photosensitive body 107, a developer 111 (an example of a developing unit), and a photosensitive body cleaning device 113 (an example of a cleaning unit) are integrally combined and held by a housing 117, and the housing 117 is provided with an attachment rail 116 and an opening portion 118 for exposure.

[0271] Note that Figure 2 , reference numeral 109 denotes an exposure device (an example of an electrostatic charge image forming unit), reference numeral 112 denotes a transfer device (an example of a transfer unit), reference numeral 115 denotes a fixing device (an example of a fixing unit), and reference numeral 300 denotes a recording paper (an example of a recording medium).

[0272] Next, a toner cartridge according to the exemplary embodiment will be described.

[0273] The toner cartridge according to the exemplary embodiment accommodates the toner according to the exemplary embodiment and is detachable from the image forming apparatus. The toner cartridge accommodates the toner for replenishment supplied to the developing unit provided in the image forming apparatus.

[0274] like Figure 1 The image forming apparatus shown has a configuration in which toner cartridges 8Y, 8M, 8C, and 8K are attached to and detachable from the apparatus, and developers 4Y, 4M, 4C, and 4K are connected to toner cartridges corresponding to the respective developers (colors) through toner supply pipes (not shown), respectively. In addition, in the case where the toner contained in the toner cartridge is low in flow, the toner cartridge is replaced.

[0275] Example

[0276] Hereinafter, the present invention will be described more specifically through embodiments, but the present invention is not limited to the following embodiments as long as it does not exceed the gist thereof. In the following description, all "parts" and "%" are based on mass unless otherwise specified.

[0277] Preparation of olefin resin containing polar groups

[0278] Polar group-containing olefin resin E-1 (Lotader (registered trademark) HX8290, produced by Arkema)

[0279] Polar group-containing olefin resin E-2 (Lotader (registered trademark) 3430, produced by Arkema)

[0280] Polar group-containing olefin resin E-3 (Lotader (registered trademark) 3410, produced by Arkema)

[0281] Polar group-containing olefin resin E-4 (Lotader (registered trademark) 4210, produced by Arkema)

[0282] Note that Table 1 shows the compositions of monomer units, acid values, and melting temperatures of the polar group-containing olefin resins E-1 to E-4.

[0283] Preparation of olefin resin particle dispersion E-1 containing polar groups

[0284] Toluene: 300 parts

[0285] ●Olefin resin containing polar groups E-1: 100 parts

[0286] The above components were mixed in a 1L separable flask and dissolved by stirring at 90°C. A solution prepared by dissolving 0.5 parts of sodium dodecylbenzenesulfonate and 0.5 parts of NN dimethylaminoethanol in 50 parts of ion exchange water and 50 parts of 2-propanol was added dropwise over 10 minutes. Furthermore, 500 parts of ion exchange water were added dropwise over 2 hours while stirring at 90°C. Thereafter, toluene was removed using an evaporator to obtain a polar group-containing olefin resin particle dispersion E-1 having a volume average particle diameter of 140 nm. The resin particle concentration of the dispersion was adjusted to 20% with ion exchange water.

[0287] Preparation of polar group-containing olefin resin particle dispersions E-2 to E-4

[0288] Polar group-containing olefin resin particle dispersions were obtained using the same method except that the polar group-containing olefin resin E-1 was changed to the polar group-containing olefin resins E-2 to E-4 in the preparation of the polar group-containing olefin resin particle dispersion E-1.

[0289] Preparation of other olefin resins

[0290] Olefin resin EV-1 (ULTRASEN (registered trademark) 685, produced by TOSOH CORPORATION)

[0291] Olefin resin EV-2 (NUCRELN1560, produced by Du Pont-Mitsui Polychemicals Co., Ltd.)

[0292] Olefin resin EV-3 (ACLIFT (registered trademark) WK402, produced by Sumitomo Chemical Company, Limited)

[0293] Note that the compositions, acid values, and melting temperatures of monomer units in other olefin resins EV-1 to EV-3 are shown in Table 1.

[0294] Preparation of olefin resin particle dispersions EV-1 to EV-3

[0295] Olefin resin particle dispersions were obtained using the same method except that the polar group-containing olefin resin E-1 was changed to olefin resins EV-1 to EV-3 in the preparation of the polar group-containing olefin resin particle dispersion E-1.

[0296] [Table 1]

[0297]

[0298] Synthesis of amorphous polyester resin P-1 (acid value: 10 mgKOH / g)

[0299] ●Bisphenol A ethylene oxide adduct: 150 parts

[0300] ●Bisphenol A propylene oxide adduct: 250 parts

[0301] ●Terephthalic acid: 100 parts

[0302] ●Tetrapropylene succinic anhydride: 130 parts

[0303] ●Trimellitic acid: 15 parts

[0304] The above monomer components were placed in a reaction vessel equipped with a stirrer, a thermometer, a condenser and a nitrogen inlet pipe, the interior of the reaction vessel was replaced with dry nitrogen, and 0.3% of tin dioctoate relative to the total amount of the monomer components was added to the reaction vessel. The temperature was raised to 235° C. for 1 hour under a nitrogen stream, the reaction was carried out for 3 hours, the pressure in the reaction vessel was reduced to 10.0 mmHg, the reaction was stirred, and the reaction was terminated when the desired molecular weight was reached.

[0305] The obtained amorphous polyester resin P-1 had a glass transition temperature of 61° C., a weight average molecular weight of 42,000, and an acid value of 10 mgKOH / g.

[0306] Preparation of amorphous polyester resin particle dispersion P-1

[0307] ●Amorphous polyester resin P-1: 100 parts

[0308] ●Methyl ethyl ketone: 60 parts

[0309] ●Isopropyl alcohol: 10 parts

[0310] The above components were charged into a reaction vessel equipped with a stirrer and dissolved at 60°C. After confirming the dissolution, the reaction vessel was cooled to 35°C, and 3.5 parts of a 10% aqueous ammonia solution were added. Next, 300 parts of ion exchange water were added dropwise to the reaction vessel over 3 hours to produce a polyester resin particle dispersion. Subsequently, methyl ethyl ketone and isopropyl alcohol were removed by an evaporator to obtain an amorphous polyester resin particle dispersion P-1.

[0311] Preparation of styrene acrylic resin particle dispersion P-2 (acid value: 10 mgKOH / g)

[0312] ●Styrene: 82 parts by weight

[0313] ●N-butyl acrylate: 18 parts

[0314] ●Methacrylic acid: 2 parts

[0315] ● n-Dodecyl mercaptan: 1 part

[0316] The emulsion polymerization of the above components is carried out in a reactor in which 2 parts of nonionic surfactant (NONIPOL 400, produced by Sanyo Chemical Industries. Ltd.) and 3 parts of anionic surfactant (NEOGENR, produced by Dai-ichi Kogyo Seiyaku Co., Ltd.) are dissolved in 510 parts of ion exchange water, and 50 parts of ion exchange water in which 4 parts of ammonium persulfate are dissolved are put into the reactor while stirring and mixing for 20 minutes. Thereafter, the inside of the reactor is replaced with nitrogen, the inside of the reactor is heated to 70° C., and the emulsion polymerization is continued for 5 hours. As a result, a styrene acrylic resin particle dispersion P-2 having a solid content of 20%, a volume average particle diameter of 201 nm, and an acid value of 10 mgKOH / g is obtained.

[0317] Preparation of release agent particle dispersion PA-1

[0318] ●Additive resin PA-1: Acid group-containing ethylene wax (HIWAX 1105A, produced by Mitsui Chemicals, Inc., acid value: 60 mgKOH / g): 60 parts

[0319] Anionic surfactant (NEOGEN RK, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.): 3 parts (60% active ingredient, 3% active ingredient relative to the release agent)

[0320] ●Ion exchange water: 150 parts

[0321] The above materials were mixed, and the release agent was dissolved at an internal solution temperature of 120°C using a pressure release type homogenizer (Gorin homogenizer manufactured by Gaulin, Inc.). Thereafter, a dispersion treatment of the mixture was performed at a dispersion pressure of 5 MPa for 120 minutes, and then at a dispersion pressure of 40 MPa for 360 minutes, followed by cooling to obtain a release agent dispersion. Ion exchange water was added to adjust the solid content to 20%, and the resultant was set as a release agent particle dispersion PA-1. The volume average particle diameter of the particles in the release agent particle dispersion PA-1 was 260 nm.

[0322] Preparation of additive resin particle dispersion PA-2

[0323] Additive resin PA-2: polyhydroxy polyolefin oligomer (Polytail (registered trademark) H, produced by Mitsubishi Chemical Corporation, hydroxyl value: 50 mgKOH / g): 60 parts

[0324] Anionic surfactant (NEOGEN RK, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.): 3 parts (active ingredient 60%, active ingredient 3% relative to the additive resin)

[0325] ●Ion exchange water: 150 parts

[0326] The above materials were mixed, and the release agent was dissolved at an internal solution temperature of 120°C using a pressure release type homogenizer (Gaulin, Gorin homogenizer manufactured by Inc.). Thereafter, a dispersion treatment of the mixture was performed at a dispersion pressure of 5 MPa for 120 minutes, and then at a dispersion pressure of 40 MPa for 360 minutes, followed by cooling to obtain a release agent dispersion. Ion exchange water was added to adjust the solid content to 20%, and the resultant was set as an additive resin particle dispersion PA-2.

[0327] Preparation of colorant particle dispersion

[0328] Cyan pigment CI Pigment Blue 15:3 (copper phthalocyanine, trade name: FASTOGEN BLUE LA5380, manufactured by DIC): 70 parts

[0329] Anionic surfactant (NEOGEN RK, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.): 5 parts

[0330] ●Ion exchange water: 200 parts

[0331] The above materials were mixed and dispersed for 10 minutes using a homogenizer (UltraTarax T50 manufactured by IKA Corporation) Ion exchange water was added so that the solid content in the dispersion was 20%, thereby obtaining a colorant particle dispersion in which colorant particles having a volume average particle diameter of 190 nm were dispersed.

[0332] Example 1

[0333] Preparation of toner particles 1

[0334] 100 parts of polar group-containing olefin resin particle dispersion E-1, 14 parts of colorant particle dispersion, 8 parts of polyaluminum hydroxide (Paho2S, produced by Asada Chemical Industry Co., Ltd.) and 400 parts of ion exchange water were mixed and dispersed in a round stainless steel flask using a homogenizer (ULTRATARAX T50, manufactured by IKA Co., Ltd.), and the inside of the flask was stirred in a heating oil bath, and the flask was heated to 50°C. It was confirmed that aggregated particles with a D50V of 5.5 μm were formed by keeping the mixture at 50°C. Then, 1N sodium hydroxide was added to adjust the pH of the system to 8.5, and then the stainless steel flask was hermetically sealed using a magnetic seal, heated to 85°C under continuous stirring, and kept for 2 hours. After cooling with ice water, the toner particles were separated by filtration, washed 5 times with ion exchange water at 25°C, and then freeze-dried to obtain toner particles 1.

[0335] Preparation of Toner 1

[0336] 100 parts of toner particles, 0.5 parts of hydrophobic silica RX50 produced by Nippon Aerosil Co., Ltd. as an external additive, and 1.5 parts of hydrophobic silica R972 produced by Nippon Aerosil Co., Ltd. as an external additive were mixed using a Henschel mixer at a peripheral speed of 20 m / s for 15 minutes, and then coarse particles were removed using a 45 μm mesh sieve to obtain Toner 1.

[0337] Preparation of vector

[0338] A resin solution was prepared by placing 2.5 parts of styrene-acrylic resin (styrene: methyl methacrylate = 10:90, Mw: 35000) in 45 parts of toluene. 0.2 parts of carbon black was put into the resin solution, and the mixed solution was finely dispersed for 30 minutes using a sand mill to prepare a dispersion. 25 parts of the dispersion were mixed with 100 parts of ferrite particles having a volume average particle size of 30 μm. In addition, the mixture was placed in a vacuum degassing kneader, stirred for 30 minutes while heating to 80°C, and further stirred under reduced pressure to remove the solvent. After removing the solvent, the mixture was sieved with a 75 μm sieve to remove aggregates, thereby obtaining a carrier.

[0339] Preparation of developer 1

[0340] 15 parts of the obtained Toner 1 and 165 parts of the obtained carrier were stirred at 20 rpm for 20 minutes using a V-blender, and sieved with a sieve having a mesh of 212 μm to obtain Developer 1 .

[0341] Example 2-Example 13 and Comparative Example 1-Comparative Example 4

[0342] Preparation of toner particles and developer

[0343] Toner particles and a developer were obtained in the same manner as in Example 1, except that the resin particle dispersion to be used and the amount thereof were changed from 100 parts of the polar group-containing olefin resin particle dispersion E-1 to the resin particle dispersion to be used and the amount thereof as shown in Table 2 in the preparation of the toner particles 1 of Example 1.

[0344] Example 14

[0345] Preparation of toner particles

[0346] Toner particles are prepared by kneading and pulverizing methods.

[0347] 35 parts of polar group-containing olefin resin E-1, 65 parts of amorphous polyester resin P-1, 14 parts of cyan pigment CI Pigment Blue 15:3 (copper phthalocyanine, trade name: FASTOGEN BLUE LA5380, manufactured by DIC) were put into a Banbury mixer (manufactured by Kobe Steel, Ltd.), pressure was applied so that the internal temperature was 110±5°C, and kneaded at 80 rpm for 10 minutes. The obtained kneaded product was cooled, fully pulverized with a hammer mill, further finely pulverized with a jet mill, and then classified with a bent pipe jet classifier (manufactured by MATSUBO Corporation). A dispersion was prepared by dispersing 100 parts of the particles in an aqueous solution prepared by adding 6.8 parts of sodium dodecylbenzenesulfonate to 550 parts of ion-exchanged water. A solution in which 0.34 parts of ammonium persulfate was dissolved in 10 parts of ion-exchanged water was added to the obtained dispersion, and a mixed solution in which 12.3 parts of styrene and 34 parts of ion-exchanged water were mixed at a temperature of 80° C. and further mixed with 2 parts of sodium dodecylbenzenesulfonate was added dropwise over 30 minutes, and the resultant was polymerized at 80° C. for 2 hours.

[0348] The reaction product was filtered, washed with ion exchange water, and dried using a vacuum dryer to obtain toner particles. Furthermore, a developer was obtained in the same manner as in Example 1 except that the toner particles were used.

[0349] For each toner of Examples and Comparative Examples, the acid value and ratio of carboxyl groups contained in maleic acid groups and maleic anhydride groups relative to the total carboxyl groups contained in the toner (hereinafter referred to as "maleic acid-derived carboxyl group ratio") were measured by the above method. The results are shown in Table 2.

[0350] evaluate

[0351] High temperature excursion evaluation

[0352] The toner application amount was adjusted to 4.5 g / m by Docucentre Color 400 manufactured by Fuji Xerox Co., Ltd. 2 The unfixed image was output. A thin film synthetic paper (Yupo paper manufactured by Yupo Corporation) was used as a recording medium. The output image was a solid image of 50 mm×50 mm and 100% image density.

[0353] As a fixing evaluation apparatus, a device modified by removing an Apeos Port IVC3370 fixing machine manufactured by Fuji Xerox Co., Ltd. so that the fixing temperature can be changed was used.

[0354] The fixing evaluation device has a nip width of 6 mm, 1.6 kgf / cm 2The unfixed image was fixed at a fixing temperature range of 160°C to 220°C at intervals of 5°C, the presence or absence of thermal offset was visually confirmed, and the lowest temperature at which thermal offset occurred was evaluated as the thermal offset occurrence temperature. The evaluation criteria are as follows.

[0355] A: The temperature at which thermal offset occurs is above 220°C

[0356] B: The thermal offset temperature is 200°C or higher and less than 220°C

[0357] C: The thermal offset temperature is 180°C or higher and less than 200°C

[0358] D: Thermal excursion temperature is less than 180°C

[0359] Low temperature excursion evaluation

[0360] The toner application amount was adjusted to 4.5 g / m by Docucentre Color 400 manufactured by Fuji Xerox Co., Ltd. 2 An unfixed image was output. A thin film synthetic paper (Yupo paper manufactured by Yupo Corporation) was used as a recording medium. The output image was a solid image of 50 mm×50 mm and 100% image density.

[0361] As a fixing evaluation apparatus, an apparatus modified by removing an Apeos Port IVC3370 fixing machine manufactured by Fuji Xerox Co., Ltd. so that the fixing temperature can be changed was used. The fixing evaluation apparatus had a nip width of 6 mm, a 1.6 kgf / cm 2 The nip thickness is 100mm / s and the processing speed is 175mm / sec.

[0362] The unfixed image was fixed at intervals of 5° C. in a fixing temperature range of 140° C. to 170° C., the presence or absence of cold offset was visually confirmed, and the lowest temperature at which cold offset occurred was evaluated as the cold offset occurrence temperature. The evaluation criteria were as follows.

[0363] A: The temperature of cold offset is below 140℃

[0364] B: The cold offset temperature is higher than 140℃ and lower than 150℃

[0365] C: The cold offset temperature is higher than 150°C and lower than 160°C

[0366] D: Cold offset occurs at a temperature below 170°C

[0367] Evaluation of bending properties (bending strength)

[0368] The toner application amount was adjusted to 13.5 g / m by Docucentre Color 400 manufactured by Fuji Xerox Co., Ltd. 2 An unfixed image was output. A thin film synthetic paper (Yupo paper manufactured by Yupo Corporation) was used as a recording medium. The output image was a solid image of 25 mm×25 mm and 100% image density.

[0369] As a fixing evaluation apparatus, a device modified by removing an Apeos Port IVC3370 fixing machine manufactured by Fuji Xerox Co., Ltd. so that the fixing temperature can be changed was used.

[0370] The fixing evaluation device has a nip width of 6 mm, a 1.6 kgf / cm 2 The nip thickness is 100mm / s and the processing speed is 175mm / sec.

[0371] The unfixed image was fixed at a fixing temperature of 90°C to 180°C at intervals of 5°C, a well-fixed image without image defects and image disorder due to peeling defects was bent, a load of 50 g was applied thereto, and the degree of image defects in the portion was observed. Then, when a fixing temperature equal to or higher than a level at which some image peeling was observed but there was no problem in actual use was evaluated as the minimum fixing temperature:

[0372] A: The minimum fixing temperature is lower than 130℃

[0373] B: The minimum fixing temperature is above 130°C and below 140°C

[0374] C: The minimum fixing temperature is above 140°C and below 150°C

[0375] D: The minimum fixing temperature is above 150°C

[0376] Evaluation of image defects at high temperature and high humidity

[0377] After leaving DocuCentreColor 400 manufactured by Fuji Xerox Co., Ltd. for one day in a low temperature and low humidity environment (10°C, 15% RH), 100,000 images with an area coverage of 1% were continuously output. Then, the image forming apparatus was placed in a high temperature and high humidity environment (30°C, 85% RH) for one day. Subsequently, 20,000 images with an area coverage of 20% were continuously output. For the 20,000 continuous images with an area coverage of 20%, a total of 100 final images were checked, and the number of sheets with image defects (such as color streaks and color loss) was counted.

[0378] A: The number of sheets with image defects ≤ 1

[0379] B: 1<Number of sheets with image defects ≤ 5

[0380] C: 5<Number of sheets with image defects ≤ 10

[0381] D: 10<Number of sheets with image defects ≤ 20

[0382] E: 20 <Number of sheets with image defects

[0383] The above description of exemplary embodiments of the present invention has been provided for the purpose of illustration and description. It is not intended to be exhaustive or to limit the present invention to the precise form disclosed. Obviously, many modifications and variations will be apparent to those skilled in the art. These embodiments are selected and described in order to best explain the principles of the present invention and its practical application, so that other technical personnel in the art can understand the various embodiments of the present invention and the various modifications suitable for the intended specific use. The scope of the present invention is defined by the appended claims and their equivalents.

[0384]

Claims

1. An electrostatic charge image developing toner, the electrostatic charge image developing toner comprising: An olefin resin containing a polar group, the olefin resin containing a polar group being a polymer of a composition comprising at least one non-polar monomer unit (X) selected from the group consisting of ethylene and α-olefins having 3 to 10 carbon atoms, a polar monomer unit (Y) having at least one of a maleic acid group and a maleic anhydride group, and a monomer unit (Z) polymerizable with at least one of the non-polar monomer unit (X) and the polar monomer unit (Y), wherein the proportion of the non-polar monomer unit (X) relative to all monomer units is 70% by weight to 90% by weight, wherein the acid value of the toner is 10 mgKOH / g to 60 mgKOH / g, and Here, the ratio of the polar group-containing olefin resin to the total mass of the resin components contained in the toner is 35 wt % to 100 wt %.

2. The electrostatic charge image developing toner according to claim 1, in, The polar group-containing olefin resin is a polymer of a composition containing, as the non-polar monomer unit (X), at least one selected from the group consisting of ethylene and α-olefins having 3 to 6 carbon atoms.

3. The electrostatic charge image developing toner according to claim 1, in, The polar group-containing olefin resin is a polymer of a composition in which the ratio of the polar monomer unit (Y) relative to the entire monomer units of the polymer is 1% by weight to 20% by weight.

4. The electrostatic charge image developing toner according to claim 1, in, The polar group-containing olefin resin is a polymer of a composition containing an acrylic acid ester represented by the molecular formula (Z1) as the monomer unit (Z), Molecular formula (Z1)H2C=C(R Z1 )-COO-R Z2 Among them, R Z1 represents a methyl group or an ethyl group, and R Z2 represents an alkyl group having 1 to 6 carbon atoms. 5 . The electrostatic charge image developing toner according to claim 1 , further comprising a polyester resin.

6. The electrostatic charge image developing toner according to claim 1, in, The polar group-containing olefin resin has a melting temperature of 65°C to 95°C.

7. The electrostatic charge image developing toner according to claim 1, in, Among all carboxyl groups contained in the electrostatic charge image developing toner, a ratio of the carboxyl groups contained in the maleic acid group and the maleic anhydride group is 10% to 100%. 8 . An electrostatic charge image developer comprising the electrostatic charge image developing toner according to claim 1 .

9. A toner cartridge configured to accommodate the electrostatic charge image developing toner according to claim 1, in, The toner cartridge is detachable from the image forming apparatus.

Citation Information

Patent Citations

  • Electrophotographic toner

    JP2000098664A

  • Toner for developing electrostatic charge image

    JP2010151899A

  • toner

    JP2017201398A

  • Powdered ink for electronic photographic development and preparation method thereof

    CN106940516A

  • Dry toner

    JP1982008549A